Social and Political Allusions in Turner’s Kirkby Lonsdale Churchyard - Sam Smiles (British Art Studies)
J.M.W. Turner’s watercolour of *Kirkby Lonsdale Churchyard* (circa 1817--18) was produced for engraving in the Rev. Thomas Dunham Whitaker’s topographical publication *An History of Richmondshire* (1823), one of twenty designs Turner contributed to that work. The squabbling schoolboys who disturb the foreground are not routine staffage figures and their presence has always provoked comment. This article proposes that Turner included them as a disguised allusion to the Tory government’s persecution of the political satirist William Hone, whose trials for blasphemy and sedition took place in December 1817. It further suggests that, by situating the incident in Kirkby Lonsdale, Turner was able to make an oblique reference to the political corruption associated with the Earl of Lonsdale’s domination of Westmorland elections. The watercolour can be added to a dozen other examples of works by Turner bearing allusions to the Reform movement, painted in the 1820s and 1830s.